Cholestatic Drug-Induced Liver Injury in a Patient Taking High-Dose Niacin for Hyperlipidemia - Nanjiba Nawaz MD; Tyler Mistretta MD; Christian Karime MD; Jason Lewis MD; Emily Wolf MD (SAGE Publishing, 2024)
Niacin, an important component of a balanced diet, is central to lipid metabolism. Occasionally used to treat hyperlipidemia, niacin is widely available without a prescription, making its use often unknown to treating physicians. Severe hepatotoxicity has been reported with niacin use. In the following report, we describe a case of hospitalization for acute decompensated cirrhosis with cholestatic morphology in a patient taking self-initiated large quantities of extended-release niacin. Despite medical management and support, the patient unfortunately expired on day 16 of hospitalization. Given ease of access and unclear long-term benefit in hyperlipidemia, the current case serves to raise awareness of niacin's potential hepatotoxicity through highlighting a severe outcome. Although mode of liver injury remains unknown, the use of extended-release niacin formulations and prolonged high-dose supplementation is associated with enhanced hepatotoxicity. Careful review and counseling of commonly available supplements remains an important task of both hospital and primary care physicians.